PENERAPAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATERI BARISAN DAN DERET DI KELAS X-IPS2 MAN RUKOH BANDA ACEH TAHUN AJARAN 2014 / 2015 - Fariha, Mutia (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
This research is a classroom action research that aims to (1) determine how to apply the model of problem based learning in order to improve student learning outcomes and (2) determine learning outcomes and student activities through the application of problem-based learning models. The subjects were students of class X-IPS2 totaling 26 people. The object of research is the study model Problem Based Learning in learning. Student learning outcome data collected through tests and analyzed descriptively. The results of the analysis after the action was obtained in the first cycle there were 11 students (42.3%), which reached the KKM. In the second cycle increased to 23 students (88.5%), which reached KKM, an increase of 42.2%. Student activity also showed an increase, in the first cycle only reached four aspects to seven aspects of the second cycle. Based on the analysis it can be concluded that the application of the model of Problem Based Learning can improve learning outcomes and student activity significantly